Milk fatty acid variability and association with polymorphisms in SCD1 and DGAT1 genes in White Fulani and Borgou cattle breeds - Houaga, I.; Muigai, Anne W.T.; Ng'ang'a, Fredrick M.; Ibeagha-Awemu, E.M.; Kyallo, Martina M.; Youssao, I.A.; Stomeo, Francesca (Springer, 2018)
The stearoyl-CoA desaturase 1 (SCD1) A293V and acyl CoA: diacylglycerol acyltransferase 1 (DGAT1) K232A polymorphisms have been associated with significant variation in bovine milk fatty acid composition and unsaturation indices in western cattle breeds. This study aimed to estimate the milk fatty acid variability in indigenous Borgou and White Fulani cattle breeds of Benin, and the effects of the SCD1 A293V and DGAT1 K232A polymorphisms on milk and fatty acid composition and unsaturation indices. Thus, 85 Borgou and 96 White Fulani cows were genotyped for the SCD1 A293V and DGAT1 K232A polymorphisms and their milk and fatty acid composition and unsaturation indices were determined. Borgou presented milk with higher linoleic acid (P < 0.001), oleic acid (P < 0.05), C18 index (P < 0.001), total unsaturation index (P < 0.05), and lower total saturated fatty acid (SFA) compared to White Fulani. The SCD1 VV genotype was associated with higher protein and lactose contents in White Fulani (P < 0.05). In Borgou, the SCD1 AV genotype was associated with higher C14 and total unsaturation indices (P < 0.01), while the SCD1 V allele was associated with decrease in C14 index (P < 0.05). In White Fulani, the SCD1 VV genotype was associated with lower C18:1 cis-9 content (P < 0.05) while the DGAT1 K allele was associated with increased total SFA (P < 0.05), and decreased C18 index (P < 0.05), total unsaturation index (P < 0.01) and total monounsaturated fatty acid (P < 0.01). The SCD1 A293V and DGAT1 K232A may serve as genetic markers to improve milk fatty acid traits in Borgou and White Fulani breeds.